2016
DOI: 10.1038/srep32391
|View full text |Cite
|
Sign up to set email alerts
|

The optical measurement of large cluster tracks in a gas jet

Abstract: We propose an optical method based on Rayleigh scattering for the direct measurement of cluster tracks produced by a high-pressure gas jet. The tracks of the argon and methane clusters are acquired by a high-speed camera. It is found that the cluster sizes of these tracks are within the range of 7E + 03~1E + 07 for argon and 2E + 06~4E + 08 for methane. Most argon tracks are continuous and their intensity changes gradually, while the majority of the methane tracks are separated into discrete fractions and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Note that the Hagena scaling law predicts a much bigger methane cluster for our experimental condition, and the ion temperature predicted using the Hagena parameter is far off the experimentally measured ion temperature of kT = 52±2 keV. This is consistent with previous studies [ 24 26 ], where the Hagena scaling law overestimates the cluster sizes in their experiments.…”
Section: Resultssupporting
confidence: 91%
“…Note that the Hagena scaling law predicts a much bigger methane cluster for our experimental condition, and the ion temperature predicted using the Hagena parameter is far off the experimentally measured ion temperature of kT = 52±2 keV. This is consistent with previous studies [ 24 26 ], where the Hagena scaling law overestimates the cluster sizes in their experiments.…”
Section: Resultssupporting
confidence: 91%
“…The first one can be clearly ruled out, since much larger clusters do not give more signal for higher values of the ellipticity. Our measurements are above the single atom regime, with the smallest cluster size having ∼11 atoms (with a certain approximation for smaller clusters, since the Rayleigh scattering method can safely identify clusters above ∼100 atoms [38,42]). Knowing this, we cannot fully exclude atom-to-neighbour recombination mechanisms, however we also have to consider that our results agree very well with those of Strelkov et al [20] using Ar monomers (atomic targets), as shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…In order to obtain supersonic gas streams it is advantageous to use de Laval nozzles. Conical nozzles were investigated in several papers [9][10][11], but the de Laval geometries received less attention. On the one hand this is due to the difficulty of fabrication which requires an electro-erosion technique, on the other hand the experiments with de Laval nozzles haven't provided definite scaling data [9].…”
Section: Cluster Size Estimations For Different Nozzle Geometriesmentioning
confidence: 99%
“…Most of the works however use a simple scaling law of Hagena [8] for the cluster size. Rayleigh scattering is an excellent method for experimental characterization of the gas jets, and even recently detailed investigations were carried out for Ar clusters using this diagnostic method [9][10][11].…”
Section: Introductionmentioning
confidence: 99%